Persepsi tentang Usia Pernikahan Perempuan dan Jumlah Anak yang Diharapkan: Mampukah Memprediksi Praktek Pengasuhan Orang Tua? - Oktriyanto, Oktriyanto; Amrullah, Hilma; Hastuti, Dwi; Alfiasari, Alfiasari (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2019)
In Indonesia, the ideal age for marriage and the number of ideal children has become an issue in family development program. This study aims to analyze the mother's perceptions of the marriage age of women and the expected number of children among families with preschool children in Indonesia and its relation to the practice of parenting. The study used secondary data from the Survey of Population, Family Planning and Family Development Program Performance, National Medium Term Development Plan Year 2017. Respondents of this study were mothers who had preschool children that were 17,886 people. The results showed that good parenting was in line with maternal characteristics such as the status of working mothers, increasingly mother's age, higher maternal education, and the number of preschoolers in the family. This study also showed that there is a relationship between parenting practices and the mother's attitude on the age marriage of women and the expected number of children. These findings indicate that maternal assessment of the age of marriage of women and the expected number of children could predict parenting practices carried out by the family. Therefore, the program to increase parenting capacity needs to consider the mother's beliefs about the age of marriage and the number of children as factors that will influence the parenting practices of the family.